Structure of Fungal α Mating Pheromone in Membrane Mimetics Suggests a Possible Role for Regulation at the Water-Membrane Interface - Partida-Hanon, Angélica; Maestro-López, Moisés; Vitale, Stefania; Turrà, David; Di Pietro, Antonio; Martínez-del-Pozo, Álvaro; Bruix, Marta (Frontiers in Microbiology, 2020)
Fusarium oxysporum is a highly destructive plant pathogen and an emerging pathogen of humans. Like other ascomycete fungi, F. oxysporum secretes α-pheromone, a small peptide that functions both as a chemoattractant and as a quorum-sensing signal. Three of the ten amino acid residues of α-pheromone are tryptophan, an amino acid whose sidechain has high affinity for lipid bilayers, suggesting a possible interaction with biological membranes. Here we tested the effect of different lipid environments on α-pheromone structure and function. Using spectroscopic and calorimetric approaches, we show that this peptide interacts with negatively charged model phospholipid vesicles. Fluorescence emission spectroscopy and NMR measurements revealed a key role of the positively charged groups and Trp residues. Furthermore, NMR-based calculation of the three-dimensional structure in the presence of micelles, formed by lipid surfactants, suggests that α-pheromone can establish an intramolecular disulfide bond between the two cysteine residues during interaction with membranes, but not in the absence of lipid mimetics. Remarkably, this oxidized version of α-pheromone lacks biological activity as a chemoattractant and quorum-sensing molecule. These results suggest the presence of a previously unidentified redox regulated control of α-pheromone activity at the surface of the plasma membrane that could influence the interaction with its cognate G-protein coupled receptor.